2019
DOI: 10.3233/adr-190109
|View full text |Cite
|
Sign up to set email alerts
|

Mild Cognitive Impairment with a High Risk of Progression to Alzheimer’s Disease Dementia (MCI-HR-AD): Effect of Souvenaid® Treatment on Cognition and 18F-FDG PET Scans

Abstract: Background: Previous studies have shown that Souvenaid (medical food) can have benefits on memory, cognition, and function in early Alzheimer’s disease (AD) and mild cognitive impairment (MCI). Objective: Demonstrate that Souvenaid could improve or maintain cognition and has an effect on neurodegeneration biomarkers. Methods: This cohort study was carried out from June 2015 through December 2016 in the Neurology Department, Infanta Cristina H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Real-world data and patient experience programs have also reported benefits for Souvenaid in patients with cognitive impairment and mild AD, including increased motivation and social engagement, improved energy levels, physical and mental resilience, and improvements in mood, cognition, and memory associated with a return to functional tasks and hobbies [105–110]. One study showed that Souvenaid was effective on behavioral and functional deficits [105], while another reported improvements in depression, anxiety, and apathy [109].…”
Section: Clinical Trials Of Souvenaidmentioning
confidence: 99%
See 1 more Smart Citation
“…Real-world data and patient experience programs have also reported benefits for Souvenaid in patients with cognitive impairment and mild AD, including increased motivation and social engagement, improved energy levels, physical and mental resilience, and improvements in mood, cognition, and memory associated with a return to functional tasks and hobbies [105–110]. One study showed that Souvenaid was effective on behavioral and functional deficits [105], while another reported improvements in depression, anxiety, and apathy [109].…”
Section: Clinical Trials Of Souvenaidmentioning
confidence: 99%
“…One study showed that Souvenaid was effective on behavioral and functional deficits [105], while another reported improvements in depression, anxiety, and apathy [109]. Furthermore, caregivers reported benefits in the Subjective Changing Scale (SCS) in patients with MCI at high risk of progression to AD taking Souvenaid [110]. It is important to note that data from these studies are not as strong as the data from randomized controlled trials.…”
Section: Clinical Trials Of Souvenaidmentioning
confidence: 99%
“…Studies involving CI participants all reported an effect of the nutritional interventions on either brain metabolism, perfusion or function ( Table 5 ). One year of Souvenaid preserved glucose metabolism in MCI, while hypometabolism was observed for the sham intervention (Manzano Palomo et al, 2019 ). Twenty-six weeks of ω-3 supplementation increased CBF in posterior regions for aMCI (Schwarz et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a cohort study of patients with MCI at risk for progression to AD used 18 F-FDG PET scans as a direct indicator of synaptic function and organization. The results found that scans of patients taking Souvenaid showed less significant worsening of glucose metabolism compared to the significant worsening of those patients who did not take Souvenaid [ 37 ]. In line with findings in preclinical studies, proton magnetic resonance spectroscopy reveals that Souvenaid affects brain phospholipid metabolism in mild AD [ 45 ].…”
Section: Discussionmentioning
confidence: 99%